Morphological and Biochemical Characterization of Wild Hop (Humulus lupulus L.) Populations from Banja Luka Area (Bosnia and Herzegovina) - Danijela Kondić; Andreja Čerenak; Iztok Jože Košir; Miha Ocvirk; Tanja Krmpot; Gordana Đurić (Agronomy, 2021)
This study aims to do a morphological and biochemical characterization of selected wild hop populations from the Banja Luka region, as plant material with potential value for introduction into plant selection. Female inflorescences (cones) from seven populations (DKH3, DKH5, DKH6, DKH8, DKH9, DKH10, and DKH11) were sampled in 2018 and 2019. Hop cones were collected in October 2018 and 2019 for morphological characterization, when 50 cones per population were analyzed, and also the cones were collected in mid-September in 2019 for biochemical characterization. Morphological parameters were carried out for: cone length (cm), number of nodes per cone spindle, cone density, and number of seeds per cone, all important agronomic characters in hop production. Also, 27 components of essential oil and 6 components of hop resins were analyzed. Statistical analysis of morphological characteristics was performed by factorial analysis of variance (year × population), and the significance of individual differences was determined by LSD test. The grouping of examined hop populations according to the manifested morphological characteristics was performed by cluster analysis. Statistical analysis for biochemical characteristics was performed by analysis of variance, and the significance of the differences was tested by Tukey’s statistical test. In order to determine similarities between different population multivariant statistical method Principal component analysis (PCA) was applied. According to morphological and biochemical analysis, DKH6 hop population is singled out as the most valuable for hop breeding.